Real-Time Shear and Normal Force Trends in Tungsten Chemical Mechanical Planarization with Different Conditioning Discs. (1st January 2018) - Peckler, L.; Mu, Y.; Stuffle, C.; Sampurno, Y.; Philipossian, A.
Abstract : In-situ conditioning is known to increase material removal rate (RR) during chemical mechanical planarization (CMP), because it roughens the pad surface that is in contact with the wafer. Previous studies have shown that the conditioning disc changes the pad surface micro-texture and affects the thermal, kinetic and tribological attributes of the CMP process. This study focuses on two different diamond discs for in-situ conditioning during tungsten CMP, and shows how real-time force data improves our understanding of the effects from using one disc versus the other. Shear and normal forces were analyzed through spectral analysis, variance and force scatter plots. Frequency signatures that appear regardless of the type of disc used were likely attributed to vibrations of the polisher and the harmonics of these vibrations. A new parameter, directivity (Δ), was employed, which highlighted the significant differences in shear force variance between the two discs. Above all, this study confirmed that high Δ correlated with high RR. Compared to a related study on copper CMP with these discs, the trends between Δ and RR seemed to continue to hold.